2010 IEEE Energy Conversion Congress and Exposition 2010
DOI: 10.1109/ecce.2010.5617862
|View full text |Cite
|
Sign up to set email alerts
|

Six-phase supply feasibility using a PM fractional-slot dual winding machine

Abstract: The growing interest on fault tolerant drives requires new solutions avoiding the adoption of custom and expensive configurations. The machine with a dual three-phase winding is an interesting candidate. It is provided of two windings, each of them fed by one converter of half power. In the event of fault, one of the two three-phase windings (the faulty one) is disconnected and the machine is operated by means of the healthy winding only. With a proper mechanical and electrical arrangement the machine can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…B 1 , B 3 Fundamental and 3rd harmonic components of excitation flux density. E 1 , E 3 Amplitude of fundamental and 3rd harmonic back-EMFs. e a , e b , e c Instantaneous three phase back-EMFs.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…B 1 , B 3 Fundamental and 3rd harmonic components of excitation flux density. E 1 , E 3 Amplitude of fundamental and 3rd harmonic back-EMFs. e a , e b , e c Instantaneous three phase back-EMFs.…”
Section: mentioning
confidence: 99%
“…e a , e b , e c Instantaneous three phase back-EMFs. I 1 , I 3 Amplitude of fundamental and 3rd harmonic current. I a Current amplitude varied with a. i a , i b , i c Instantaneous three phase currents.…”
Section: mentioning
confidence: 99%
“…Thus, it helps to reduce the thermal stresses on power devices and provides the employment of smaller converters. Most importantly, reliability and redundancy are the key features for multi-phase machines with multiples of three so that the machine can continue to operate even with one or more un-healthy stator winding sets [1]. These features make fault tolerant multiphase PM motors become more attractive for safety-critical applications such as space, traction, military and etc.…”
Section: Introductionmentioning
confidence: 99%
“…As reliability is critical for transportation applications, these PM topologies can also be compliant for dual channel windings and fault tolerant modes. In these two cases, several studies have shown that some PMSM designs are appropriate [6], [10], [11]. Another aspect concerns the manufacturing process of PMSM having FSCW.…”
Section: Introductionmentioning
confidence: 99%